Challenges of internationalization of the Indonesian museum guides' communication skills competency - Nugraheni, Nur Endah; Makhasi, Ghifari Yuristiadhi Masyhari; Soelistiyowati, Endang; Chen, Shu-Chuan; Chen, Mei-Ru; Chang, Chia-Chen (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
As the front guards, museum guides need to master many skills that support the role of transferring information in the museum to every visitor who comes, both domestic and foreign. More specifically, every museum guide must master foreign language skills in order to serve foreign visitors. Unfortunately, not all museum guides have foreign language skills, especially English, and other supporting skills such as curation, communication, and public speaking. This paper investigates the limited ability of English mastery and other supporting skills of museum guides in two government-owned museums in Yogyakarta, the second tourism city in Indonesia, and how far they affect the internationalization of the two museums as representatives of other museums in Indonesia. This descriptive research uses data collection methods in surveys with questionnaires and in-depth interviews with guides and visitors of the museum, both domestic and foreign. This research found that limited foreign language skills, especially English and other professional skills of museum guides, can slow down the museum's internationalization process in Indonesia.